HEYKEL SANATINDA METODOLOJİK YAKLAŞIM BAĞLAMINDA TAMAMLANMAMIŞLIK/EKSİKLİK KURAMININ DEĞERLENDİRİLMESİ - UYSAL, Üyesi Hülya (TURAN : stratejik arastirmalar merkezi, 2023)
The determination of art in the cultural context takes place by filling it with social content. Art is not only a beauty, entertainment, healing or utopia, but also a religious ceremony, a war, a moral-educational activity or a phenomenological witness of a concrete life process. Art always presents in society and is an important element in reinforcing social relations. Art is a part of the whole (life). It is an important tool/element/object for people to express their thoughts. In this context, it is required to evaluate the phenomenon of incompleteness in the work of art with a methodological approach within the framework of the sculpture discipline, which is the witness of the relationship between human, society and art. The concept of incompleteness, which appears formally in the art of sculpture, is not an existing emptiness, but an indicator that questions the existing ones. In the work of art, there are consciously left incompleteness, or contents in incompleteness. This content, in the artwork, requires not only the representation of the formal deficiency, but also the modern and postmodern perspective. In this context, what seems like incompleteness is actually expanding our way of perception and corresponds to the filling of the inside to the outside or the outside to the inside via opening the point of breaking in art. Incompleteness in a work of art is a smooth transition point between the work of art and life. By breaking the rigid and clear framework of disciplines such as painting and sculpture, or leaving the elements of the modernist perspective, it reconstitutes and dissolves (destroys the old perspective) with a new perspective, namely the postmodern perspective, by disrupting this solid and clustered structure. With the theory of incompleteness, German philosopher Kurt Gödel questions the possibility of experiencing the "other" world and reaching beyond it with a paradoxical point of view and sees it as the reality of abstraction. The abstract is as concrete as the concrete, and it forms the content of the theoretical one by being articulated with the functioning of the other reality in the artistic context. In this research, it is argued that the conscious incompleteness in the work of art corresponds to the paradoxical situation in the work and the social reality of its formal construction, not a flaw, but a concept, and also focused on the connections related to this argument. In this context, it is aimed to bring different perspectives to the subject by giving examples from prominent artists and their works.